Role of Kisspeptin and Neurokinin B in Puberty in Female Non-Human Primates - Terasawa, Ei; Garcia, James P.; Seminara, Stephanie B.; Keen, Kim L. (Frontiers in Endocrinology, 2018)
In human patients loss-of-function mutations in the genes encoding kisspeptin (KISS1) and neurokinin B (NKB) and their receptors (KISS1R and NK3R, respectively) result in an abnormal timing of puberty or the absence of puberty. To understand the neuroendocrine mechanism of puberty we investigated the contribution of kisspeptin and NKB signaling to the pubertal increase in GnRH release using rhesus monkeys as a model. Direct measurements of GnRH and kisspeptin in the median eminence of the hypothalamus with infusion of agonists and antagonists for kisspeptin and NKB reveal that kisspeptin and NKB signaling stimulate GnRH release independently or collaboratively by forming kisspeptin and NKB neuronal networks depending on the developmental age. For example, while in prepubertal females kisspeptin and NKB signaling independently stimulate GnRH release, in pubertal females the formation of a collaborative kisspeptin and NKB network further accelerates the pubertal increase in GnRH release. It is speculated that the collaborative mechanism between kisspeptin and NKB signaling to GnRH neurons is necessary for the complex reproductive function in females.